The impact of load-PV profile resolution on distribution system risk assessment - Yixiong Jia; Zhifeng Liang; Xuesong Huo; Wenjin Chen; Yun Chai; Ruoying Yu (Energy Reports, 2023)
Risk assessment is utilized to evaluate the risk level of the system and guide further operation and planning of utilities. However, to lower the cost of communication and storing, only a coarse resolution profile of load and PV can be collected and used to evaluate the risk level of the system, which may lead to inaccurate assessment. To this end, this paper investigates the impact of load-PV profile resolution on distribution system risk assessment. A super-resolution Generative Adversarial Network with pre- and post-processing processes is proposed to restore the high-frequency component of the load-PV profile. Then, with the generated high-resolution profile, a risk assessment model based on the exterior point method is proposed to evaluate the risk level of the distribution system. Case studies in a modified 33-bus system showed that the proposed super-resolution method could achieve the best performance to restore the peak values and high-frequency component of the load-PV profile compared to the other four methods. In addition, compared to super-resolution Generative Adversarial Networks without the post-processing process, the accuracy of risk assessment can be significantly improved using the proposed super-resolution method, which proves that the post-processing process is necessary.